Accreditation and competency‐based education. Issue 1 (April 2016) - Eaton, J.S.
Abstract : Background: Competency‐based education or CBE is, an approach to teaching and learning that awards credit on the basis of mastery of clearly defined competencies or skills (EDUCAUSE, 2014). The current increased emphasis on CBE is resulting in institutions and programs taking fresh approaches to their academic activity. The Council for Higher Education Accreditation (CHEA) sought to learn more about how the increased emphasis was affecting institutional and programmatic accreditation. Method: During September 2015, CHEA conducted an email survey of the 85 institutional and programmatic accreditors that are scrutinized for quality ("recognized") by either CHEA or the U.S. Department of Education. The accreditors were asked four questions about the role that their organizations play in CBE and their view about the future of CBE. Results: Of the 85 recognized accrediting organizations, 26 (30.5%) responded to the survey. This included five of the seven regional accreditors, three of the four faith‐related accreditors, three of the seven career‐related accreditors, and 15 of the 67 programmatic accreditors. Conclusions: Accreditation involvement in CBE is at present very modest and responsive in nature. The institutions and programs that decide to pursue a competency‐based approach turn to their accreditors for needed review and approval. If the accreditor is reviewing CBE that involves access to federal aid for students, the accreditor has a number of federal obligations to meet. Accrediting organizations neither require a CBE approach nor are they framing common expectations at the institutional or programmatic level for such an approach.